طلاق الثلاث في المجلس الواحد-دراسة فقهية مقارنة - - غريب, اسماعيل; غريب, حمزة; بن الصادق, عبد المطلب (University of Eloued-جامعة الوادي, 2015)
تناول هذا البحث مسألة الطلاق الثلاث في المجلس الواحد، وذلك بد ا رسة فقهیة مقارنة؛ وهذا من خلال ذكر أقوال الفقهاء التي انقسمت إلى أربعة أقوال، كان ال ا رجح منها أ ري الجمهور القاضي بإیقاع الثلاث، وذلك خلافا لما هو في باقي المذاهب؛ حیث جاء هذا البحث في ثلاثة مباحث في كل مبحث ثلاثة مطالب؛ وقد خُصِّصَ المبحث الأول للحدیث عن ماهیة الطلاق، وذلك من حیث تعریفه، ومشروعیته، وحكمه وأركانه، وحكمة من مشروعیته وسبب جعله بید الرجل، بینما عُني المبحث الثاني بالحدیث عن حكم الطلاق الثلاث في المجلس الواحد، وذلك من حیث تصویر المسألة ومحل الن ا زع و آ ا رء الفقهاء فیها، و أدلة كل فریق ومناقشتها، والقول ال ا رجح وسبب الخلاف والنظرة المقاصدیة، وخصص المبحث الثالث للحدیث عن أسباب الطلاق وآثاره والعلاج للحد منه. Summary This research adresses an issue of divorce by three statements .Tt is a comarative study by which we introduce the religious schientists' opinions which split into four different goups. There is consunsus among religious scientists concering the divorce by three statements., however, some scholars didnt agree on it since this kind of divorce accures on the same time and place. This research is devided into three parts..The first part defines divorce in terms of its meaning , nature , types and purposes. The second part intends to clarify the three divorce judgment by investigating the issue , and stating the arguments of each opposing group, and finding the reasons behind the variey of opinions about the problem. Finally, we feel need to mention the poweful opinion of the matter.The last part aims to mention the reasons and causes of divorce and effects then the sollutions of this social problems.
مذكرة ليسانس
Keywords: طلاق /المجلس/الواحد /ثلاث; Divorce/concile/un/Divorce/concile/un/trois